2016
DOI: 10.4103/2278-330x.181625
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of operable oral cavity cancer and impact of maintenance metronomic chemotherapy: A retrospective study from rural India

Abstract: Background:Oral cavity cancer is the most common cancer among rural India. There is a paucity of data for outcomes of operable oral cavity cancer from rural India. Use of maintenance metronomic may delay or avoid relapse.Aim:To evaluate outcomes of operable oral cavity carcinoma and evaluate impact of maintenance metronomic chemotherapy.Objectives:To evaluate disease-free survival (DFS), overall survival (OS), and factors affecting the outcome in operable oral cavity cancer.Materials and Methods:Data of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The disease-free survival rates were 86,5% in metronomic group versus 71.6% in control group, showing a statistical significance [242]. A similar study from India enrolling operable oral cavity cancer with maintenance metronomic therapy showed a median DFS of 13 months [243]. For head and neck cancer, another study evaluated metronomic oral regimen of methotrexate, erlotinib, and celecoxib in palliative treatment of patients with head and neck cancers and ineligible for MTD.…”
Section: Resultsmentioning
confidence: 99%
“…The disease-free survival rates were 86,5% in metronomic group versus 71.6% in control group, showing a statistical significance [242]. A similar study from India enrolling operable oral cavity cancer with maintenance metronomic therapy showed a median DFS of 13 months [243]. For head and neck cancer, another study evaluated metronomic oral regimen of methotrexate, erlotinib, and celecoxib in palliative treatment of patients with head and neck cancers and ineligible for MTD.…”
Section: Resultsmentioning
confidence: 99%
“…In unresected stage III/IVA/IVB HNSCC, concurrent CRT and lapatinib followed by lapatinib (1500 mg once daily) demonstrated improvement in CRR at six months post-CRT and median PFS in p16-negative disease, but no significant benefit in OS [ 25 ]. In India, maintenance with metronomic oral methotrexate and celecoxib in advanced oral cancer improved both DFS and OS [ 26 , 27 , 28 ]. However, the phase III randomized trial revealed that long-term lapatinib maintenance therapy provided no additional benefits in patients with surgically treated high-risk HNSCC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 48% of lung cancers and 39% of head-and-neck cancer patients smoked, predominantly bidi, which is similar to smoking prevalence seen in another major epidemiological Indian study of lung cancer (48%) and higher compared to that seen in oral cavity cancers in rural Indian population (27%), respectively. [17,18] Among several cancer cohorts studied, lung and head-and-neck cancers were the first and second cohorts, respectively, in terms of a higher percentage of patients among them having a history of smoking. As it is a cross-sectional study, the tolerance of smokers to antineoplastic drugs, including radiotherapy and surgery, compared to nonsmokers could not be illustrated.…”
Section: Discussionmentioning
confidence: 99%